Case report series: management of complete ureteral avulsion with review of the relevant literature - İbrahim Ünal Sert; Arif Aydın (African Journal of Urology, 2020)
Abstract Background Endoscopic operations and ureteroscopy have become the first choice for ureteral calculi and ureter-related operations. The ratios of the complications, which are mostly iatrogenic, range between 9 and 11%. Total ureteral avulsion during URS is quite rare with a prevalence of 0–0.3%. We present three total ureteral avulsions we experienced in our clinic during the last 2 years and their treatment. Case presentation During the last 2 years, we experienced three total ureteral avulsions: one of these occurred in our clinic and the other two occurred in an external center and were referred to us. In two cases, the omental flap was rotated after ureteral reimplantation and the ureter was completely wrapped inside the omental flap. In the third case, boari flap was formed from the bladder. Due to the presence of extrarenal wide renal pelvis, anastomosis was made with boari flap after a y–v flap was rotated on the renal pelvis. D-J stents of the patients were removed at the end of 3 months. Although there was mild hydronephrosis, parenchymal thinning and a significant decrease in functions were not observed. Ureteral avulsion of the patients was successfully managed without the need for nephrectomy. Conclusion Ureteral avulsion management is an extremely difficult condition for both the surgeon and the patient. So, the most important thing is to prevent ureteral avulsion. Ureteroplasty and omental flap treatment are applicable methods with quite successful results for complete ureteral avulsions.